2017
DOI: 10.1097/jnr.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Levels of Risky Drinking in Adolescent Alcohol Users in Taiwan: A Secondary Data Analysis

Abstract: Decreasing the availability of alcohol, developing appropriate alcohol expectancies, and increasing alcohol refusal skills may help decrease the development of high-risk drinking behavior in adolescents. Our study furthers the understanding of underage alcohol use in societies with low alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In the study conducted in Taiwan, 9.55% were classified with high-risk drinking behavior, 22.51% were classified with medium-risk drinking behavior, and 67.94% were classified with low-risk drinking behavior [12]. In a study conducted in Hong Kong, they found that high family affluence was associated with wine and spirits drinking.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted in Taiwan, 9.55% were classified with high-risk drinking behavior, 22.51% were classified with medium-risk drinking behavior, and 67.94% were classified with low-risk drinking behavior [12]. In a study conducted in Hong Kong, they found that high family affluence was associated with wine and spirits drinking.…”
Section: Discussionmentioning
confidence: 99%